1990
DOI: 10.1017/s002202990002954x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of machine-induced changes in thickness of the bovine teat

Abstract: Machine milking induced repeatable, short-term changes in thickness of the teat apex. These changes were measured with a spring-loaded caliper instrument under milking conditions that imposed differing forces on the teat apex. The mean percentage changes in teat end thickness (relative to the premilking values for individual teats) varied from 10% decrease up to 20% or more increase depending on the particular milking system used. The overall decrease in teat end thickness associated with cannula milking, milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 6 publications
5
66
0
4
Order By: Relevance
“…Similar results were reported by Peris et al (2003a,b) in the Manchega sheep breed (-0.38 mm) in a working vacuum of 36 kPa. In cows Hamann and Mein (1990) found an increase in TEWT after milking that was 2% at 30 kPa, 8% at 50 kPa and 21% at 70 kPa. Later, Hamann et al (1993) also found that the teats of cows were significantly thicker in higher vacuum levels.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Similar results were reported by Peris et al (2003a,b) in the Manchega sheep breed (-0.38 mm) in a working vacuum of 36 kPa. In cows Hamann and Mein (1990) found an increase in TEWT after milking that was 2% at 30 kPa, 8% at 50 kPa and 21% at 70 kPa. Later, Hamann et al (1993) also found that the teats of cows were significantly thicker in higher vacuum levels.…”
Section: Discussionmentioning
confidence: 86%
“…For all dams, every 2 weeks during both the morning and the afternoon milking the teat end wall thickness (TEWT) was measured with a cutimeter before and after milking (Hamann and Mein, 1990;Marnet et al, 1999). Differences in the thickness before and after the milking were calculated, and the percentage change in post-milking TEWT was calculated as proposed by Hamann et al (1996b).…”
Section: Equipment and Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure should be high enough to allow the massage effect on the teat end when the liner is closed. Blood and lymph vessels and the extracellular spaces in the teat tissue are dilated as the intra-and extravascular fluid accumulates in the teat tissue during milking (Hamann & Mein 1990;Zecconi et al 1992;Koning & Ipema 2000;Neijenhuis et al 2001). If the massage effect of the liner is insufficient, the fluid stays in the teat tissue, and changes of the pliability of the teat tissue cause a decrease in the resistance of the teat canal to bacterial invasion (O'Shea 1987;Neijenhuis 2004).…”
Section: Vacuum Dropsmentioning
confidence: 99%
“…Congestion, increased teat-end callosity, hyperkeratosis, teat orifice erosion or cyanotic teat ends seem to lead to an increased risk of udder infection. Damaged tissue regions provide good physical conditions (Langlois et al 1981;Natzke et al 1982;Bulletin of the International Dairy Federation 215 1987;Hamann & Mein 1990;Zecconi et al 1992;Neijenhuis 2004) and allow direct adherence of pathogens to colonize the teats and to invade the udder (Neave et al 1969;Bramley et al 1979;Myllys et al 1994).…”
Section: Influences Of Teat-end Vacuum On Teat-end Thickness Hyperkementioning
confidence: 99%